Trackage modelling and algorithms for finding the shortest train route - Antonin Kavicka; Ludmila Janosikova (Communications - Scientific letters of the University of Zilina, 1999)
This paper deals with two models of track network in a railway station and algorithms for finding the shortest train route. In the first model - a weighted digraph - two vertices represent a track or a switch track. Edges of a digraph are understood as the possible transitions between tracks. In the second model - a non-oriented edge weighted graph - the edges represent tracks and the vertices match the connections between tracks. Algorithms for finding a shortest route were designed and verified for both models. These algorithms respect rules for the movement of rail vehicles, as well as their length and the occupation of tracks by other rolling stock.